Audit Committee Independence, Financial Expertise, Share Ownership and Financial Reporting Quality: Further Evidence from Nigeria - Kibiya, Muhammad Umar; Che-Ahmad, Ayoib; Amran, Noor Afza (International Journal of Economics and Financial Issues, 2016)
This study investigates the characteristics of audit committee and its effect on the quality of financial reporting of Nigerian listed firms. We employed multivariate regression as a tool for analysis. The sample for the study was 101 firm-years longitudinal panels of 505 observations of non-financial listed companies on the Nigerian Stock Exchange for the period 2010 to 2014. The McNicholas (2002) measure of earnings quality was adopted to examine the monitoring mechanisms on the quality of financial reporting. The results show that control variables of company age and company size significantly affect the quality of financial reporting. The audit committee, share ownership, and financial expertise was also significant, indicating that audit committee monitoring mechanisms influence the quality financial reporting of listed non-financial firms in Nigeria. Share ownership proved to be a good motivator for audit committee members making them to be more vigilant, enthusiastic and active in their monitoring responsibilities. Keywords: Audit Committee, expertise, share ownership. JEL Classifications: E6, M4